Cover, Content, and Editorial Note from Pengabdianmu J Pengabdian Masyarakat Vol. 7 No. 1 January 2022 - Chief Editor of PengabdianMu J Pengabdian Masyarakat (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Assalamu’alaikum Wr. Wb. Dear reader, now PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat re-published on Volume 7 Issue 1 January 2022. This edition marks a change in publication frequency from four times to six times a year. The publication of PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat certainly participates in disseminating the results of community services in science and technology development conducted by lecturers and researchers especially from UMPR and other universities. This edition contains 17 articles consisting of Education, Social and Political, Agriculture, and Health Science topics. Editorial boards are fully aware that there is still room for improvement in this edition, hence with all humility willing to accept constructive suggestions and feedback for improvements to the publication for the next editions. The editorial board would like to thank the University, all editors and reviewers, and contributors of the scientific articles who have provided the repertoire in this issue. We hope that all parties, especially the contributors of the articles, could re-participate the success of the publication in the next edition in March 2022. Wassalamu’alaikum Wr. Wb.